ГРОШОВИЙ ОБІГ В УКРАЇНІ: СУЧАСНИЙ СТАН, ПРОБЛЕМИ ТА НАПРЯМИ УДОСКОНАЛЕННЯ ОРГАНІЗАЦІЇ - Чайковський, Ярослав Іванович (Науковий журнал «Світ фінансів», 2018)
Чайковський Я. І. Грошовий обіг в Україні: сучасний стан, проблеми та напрями удосконалення організації. Досліджено розвиток грошового обігу в Україні у 2013–2017 рр. Проведено аналіз динаміки грошових показників та визначено переваги готівкових розрахунків. Визначено чинники, які впливають на рівень готівки, та переваги безготівкових розрахунків для всіх учасників грошових відносин в економіці. Розкрито пріоритетне завдання Національного банку України щодо прийняття проекту Сashless economy. На основі проведеного аналізу грошового обігу зроблено висновки щодо скорочення готівкового грошового обігу та розвитку безготівкових розрахунків в Україні. Чайковский Я. И. Денежное обращение в Украине: современное состояние, проблемы и направления совершенствования организации. Исследовано развитие денежного обращения в Украине в 2013–2017 гг. Проведен анализ динамики денежных показателей и определены преимущества наличных расчетов. Определены факторы, влияющие на уровень наличности, и преимущества безналичных расчетов для всех участников денежных отношений в экономике. Раскрыто приоритетную задачу Национального банка Украины относительно принятия проекта Сashless economy. На основании проведенного анализа денежного обращения сделаны выводы по сокращению наличного денежного обращения и развитию безналичных расчетов в Украине. Chaykovskyi Ya. Money circulation in Ukraine: current status, problems and directions for improvement of organization. Introduction. One of the most effective means to solve the acute problems of the modern stage of Ukraine’s economic development is the rational organization of monetary circulation. The solution to this problem lies in the scope of the National Bank of Ukraine measures aimed, on the one hand, on improvement of cash circulation of money and, on the other hand, the development of cashless settlements. The purposeof the article is to study the current state of money circulation in Ukraine, identify the most significant problems and definition specific areas for improvement of the operation of banks with cash and the development of cashless payments, in particular, through bank payment cards. Results. The dynamics of money outside the banks, money supply, household income and gross domestic product (GDP) in Ukraine for the period of 2013-2017 has been analyzed. The dynamics of monetary indicators in Ukraine are analysed and the advantages of cash settlements are determined. The dynamics of general data on the number of participating banks of card payment systems, clients, the total number of payment cards and payment devices, types of payment cards issued by Ukrainian banks by types of information carriers, the amount and number of transactions using payment cards has been analyzed for the period 2013-2017. Conclusions. The advantages of cash settlements have been determined. The factors of increase of quantity of cash in circulation in the country are revealed. The components of cost of cash payments and the advantages of cashless payments for participants in monetary relations in the economy are determined. The priority task of the National Bank of Ukraine on reducing the volume of cash circulation, its streamlining and development of cashless settlements through the adoption of the Cashless economy project is disclosed. Based on the analysis of the development of monetary circulation in modern conditions, conclusions were made regarding the reduction of cash circulation and the development of cashless settlements in Ukraine.